Dentifrices for children differentially affect cell viability in vitro - Cvikl, Barbara (Clin Oral Investig, 2016)
OBJECTIVES: Child dentifrices vary in their composition, with possible differential impacts on cells in the oral soft tissue. While cytotoxicity studies have been performed on adult dentifrices, no respective studies have thus far been reported on child dentifrices. MATERIAL AND METHODS: Seventeen commercial dentifrices for children up to 12 years of age were evaluated with respect to their in vitro cytotoxicity on gingival fibroblasts, oral squamous cell carcinoma HSC-2 cells, and L929 mouse fibroblasts. Proliferation was analyzed and live-dead staining was performed. RESULTS: Ten child dentifrices greatly reduced cell viability with LC50 values below 5 %. Four dentifrices showed a moderate cytotoxicity with LC50 values between 5 and 20 %. Three child dentifrices showed almost no cytotoxicity with LC50 values above 95 %. The results of the assays for proliferation and live-dead staining supported these findings. CONCLUSIONS: The different composition of the child dentifrices translated into a broad spectrum of in vitro cytotoxicity on cells of the oral cavity. CLINICAL RELEVANCE: The in vitro data provide the scientific foundation for further in vivo research testing the clinical relevance of the present findings.